Christmas without snow (Digiview Productions, 2004)
Set in San Francisco (where it never snows), Michael Learned ('The Waltons') plays a recently divorced single mother trying to make sense of her life and failings. The film follows Learned and the lives of her fellow church choir members as they prepare for an important performance of Handel's 'The Messiah', under the guidance of their perfectionist choirmaster, John Houseman. Unable to balance the pressure in her life, Learned contemplates quitting the group, when a series of events take place with the effect of reaffirming her faith and belief in herself. Christmas Without Snow is intelligently acted and works from a strong script that tugs at the heartstrings.